The effect of chelator type on in vitro receptor binding and stability in 177Lu‐labeled cetuximab and panitumumab. (29th May 2014) - Novy, Zbynek; Laznickova, Alice; Mandikova, Jana; Barta, Pavel; Laznicek, Milan; Trejtnar, Frantisek
<x xml:space="preserve">Abstract</x> Monoclonal antibodies are used in the therapy of various diseases. Thanks to their high specific uptake in target tissues, these antibodies can be utilized in targeted radioimmunotherapy as carriers of radioisotopes to tumors. However, important characteristics of antibodies such as target binding and stability in the organism may be affected by various structural parameters. This study has focused on the potential influence of selected chelators on radiochemical quality and in vitro receptor binding capacity in two modified monoclonal antibodies—cetuximab and panitumumab, both ligands of the epidermal growth factor receptor (EGFR). These two antibodies were each coupled with three macrocyclic chelators (1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid, 1, 4, 7‐triazacyclononane‐1, 4, 7‐triacetic acid, and 3, 6, 9, 15‐tetraazabicyclo[9.3.1]‐pentadeca‐1(15), 11, 13‐triene‐4‐(S)‐(4‐isothiocyanatobenzyl)‐3, 6, 9‐triacetic acid) and labeled with lutetium‐177. The stability of the preparations was checked, and the cell binding to EGFR‐expressing cell lines was examined. The used method led to very stable radiolabeled preparations. The results showed that binding to the target cells was not affected by the type of chelator. All three chelators may be useful for the labeling of cetuximab and panitumumab with lutetium‐177 in future preclinical or clinical studies. Our study revealed previously unpublished fact that the type of chelator selected does not affect binding of EGFR‐targeted antibodies labeled with lutetium‐177. Copyright © 2014 John Wiley & Sons, Ltd.